What about law? : studying law at university - Barnard, Catherine; O'Sullivan, Janet; Virgo, G. J. (London, England : Zed Books, 2021)
"?' What About Law? ' succeeds where so many legal guidebooks fail ... [it] skilfully demystifies the law and ably proves its argument. The law is, indeed, all around us - and this book will whet your appetite to find out how and why.? ? Alex Wade, The Times (of the previous edition) Law is one of the few subjects that the school leaver, choosing a degree course, will have very little real understanding of. This book comes to the rescue by clearly setting out what a prospective law student can expect and why a student should choose to study law. This new edition is updated to reflect the reality of studying law today, highlighting changes due to Brexit and reforms to constitutional law. The book covers the compulsory subjects every law student has to study: contract, criminal, property and trusts law, and brings them up to date. With a clear core structure and approach it takes a case from each of these subjects to illustrate legal issues and methodology. The writing style is accessible and has the audience ? novices to law ? firmly in mind. What About Law? shows how the study of law can be fun, intellectually stimulating and challenging. It introduces prospective students to the legal system, legal reasoning, critical thinking and argument. Written by a team of experienced teachers, this book should be read by every student about to embark on the study of law."--
1 Introduction to Law -- 2 Criminal Law -- 3 Law of Contract -- 4 Tort -- 5 Land Law -- 6 Equity -- 7 Constitutional Law -- 8 European Union Law -- 9 Conclusions: Drawing Some Threads Together -- Epilogue
Includes bibliographical references and index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Law -- Study and teaching -- Great Britain; Legal skills & practice; Electronic books